Who achieves low risk drinking during alcohol treatment? An analysis of patients in three alcohol clinical trials. (26th June 2017) - Witkiewitz, Katie; Pearson, Matthew R.; Hallgren, Kevin A.; Maisto, Stephen A.; Roos, Corey R.; Kirouac, Megan; Wilson, Adam D.; Montes, Kevin S.; Heather, Nick
Abstract: Background and aims: There is evidence that low‐risk drinking is possible during the course of alcohol treatment and can be maintained following treatment. Our aim was to identify characteristics associated with low‐risk drinking during treatment in a large sample of individuals as they received treatment for alcohol dependence. Design: Integrated analysis of data from the Combined Pharmacotherapies and Behavioral Intervention (COMBINE) study, Project MATCH (Matching Alcoholism Treatments to Client Heterogeneity) and the United Kingdom Alcohol Treatment Trial (UKATT) using repeated‐measures latent class analysis to identify patterns of drinking and predictors of low‐risk drinking patterns during treatment. Setting: United States and United Kingdom. Participants: Patients ( n  = 3589) with alcohol dependence receiving treatment in an alcohol clinical trial were primarily male (73.0%), white (82.0%) and non‐married (41.7%), with an average age of 42.0 (standard deviation = 10.7). Measurements: Self‐reported weekly alcohol consumption during treatment was assessed using the Form‐901 and validated with biological verification or collateral informants. Findings: Seven patterns of drinking during treatment were identified: persistent heavy drinking (18.7% of the sample), increasing heavy drinking (9.6%), heavy and low‐risk drinking (6.7%), heavy drinking alternating with abstinence (7.9%), low‐risk drinking (6.8%), increasing low‐risk drinking (10.5%) and abstinence (39.8%). Lower alcohol dependence severity and fewer drinks per day at baseline significantly predicted low‐risk drinking patterns [e.g. each additional drink prior to baseline predicted a 27% increase in the odds of expected classification in heavy drinking versus low‐risk drinking patterns; odds ratio = 1.27 (95% confidence interval (CI) = 1.10, 1.47, P  = 0.002]. Greater negative mood and more heavy drinkers in the social network were significant predictors of expected membership in heavier drinking patterns. Conclusions: Low‐risk drinking is achievable for some individuals as they undergo treatment for alcohol dependence. Individuals with lower dependence severity, less baseline drinking, fewer negative mood symptoms and fewer heavy drinkers in their social networks have a higher probability of achieving low‐risk drinking during treatment.